Association of Lp‐PLA2 G994T gene polymorphism with risk of ischemic stroke in Chinese population. Issue 12 (28th September 2017) - Ni, Jing; Gu, Hong; Hu, Wuhao; Zhou, Fang; Zhu, Xue; Wang, Ke
Abstract: The association between lipoprotein‐associated phospholipase A2 (Lp‐PLA2) G994T gene polymorphism and the risk of ischemic stroke is unclear. The aim of this study is to investigate the influence of Lp‐PLA2 G994T genetic variant on the pathogenesis of ischemic stroke in Chinese population. A total of 348 patients with a clinical diagnosis of ischemic stroke and 260 gender‐matched control subjects under physical examination were recruited from hospitals and genotyped for G994T gene polymorphism. The results showed that there was a significant difference in the genotype distribution between the two groups and people with GT or TT genotype were associated with the higher risk of ischemic stroke even after adjusting the effects of potential confounding factors. In addition, both ischemic stroke patients and control subjects carrying T allele showed relatively lower Lp‐PLA2 activity and higher oxLDL level. Therefore, Lp‐PLA2 G994T gene polymorphism may be an independent risk factor of ischemic stroke in Chinese population.